2012
DOI: 10.1186/1471-2229-12-163
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and enzymatic changes associated with carbon mobilization, utilization and replenishment triggered in grain amaranth (Amaranthus cruentus) in response to partial defoliation by mechanical injury or insect herbivory

Abstract: BackgroundAmaranthus cruentus and A. hypochondriacus are crop plants grown for grain production in subtropical countries. Recently, the generation of large-scale transcriptomic data opened the possibility to study representative genes of primary metabolism to gain a better understanding of the biochemical mechanisms underlying tolerance to defoliation in these species. A multi-level approach was followed involving gene expression analysis, enzyme activity and metabolite measurements.ResultsDefoliation by insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 112 publications
6
47
0
Order By: Relevance
“…It is shown that grain yield in amaranth was not reduced after the mechanical removal (by hole punching) of 20-to-100% of its leaves at the pre-flowering stage. This study complemented previous reports describing the high tolerance to defoliation shown by grain amaranths [20], [36]. Moreover, the results herewith shown indicate that tolerance may be genetically determined, since different degrees of tolerance between two grain amaranth species examined were observed.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is shown that grain yield in amaranth was not reduced after the mechanical removal (by hole punching) of 20-to-100% of its leaves at the pre-flowering stage. This study complemented previous reports describing the high tolerance to defoliation shown by grain amaranths [20], [36]. Moreover, the results herewith shown indicate that tolerance may be genetically determined, since different degrees of tolerance between two grain amaranth species examined were observed.…”
Section: Introductionsupporting
confidence: 91%
“…The trays were maintained in a growth chamber kept at 26°C and 75% relative humidity (R.H.). Amaranth plantlets were subsequently transplanted to 12-L plastic pots, containing a sterile substrate [20], 21-days after germination. They were fertilized once, one week after transplant, with 400 mL of a 20: 10: 20 (N: P: K) nutrient soil drench solution prepared according to the manufacturer's instructions (Peters Professional; Scotts-Sierra Horticultural Products, Marysville, OH, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Similarly, in grain amaranth (Amaranthus cruentus), foliar herbivory induced a local increase in cytoplasmic invertase and amylolytic enzyme activities (Castrillon-Arbelaez et al, 2012). Furthermore, this study showed lower concentrations of monosaccharides, Suc, and starch in local tissues in the days after herbivore infestation.…”
Section: Carbohydrate Metabolismsupporting
confidence: 49%
“…Although both approaches generate large amounts of data, they are also inherently limited. For example, Castrillon-Arbelaez et al (2012) found little correlation between transcript abundance and enzymatic activities when studying herbivore-induced changes in carbohydrate metabolism. Similarly, Coppola et al (2013), from among a thousand differentially expressed transcripts and 87 differentially abundant proteins, found only three transcript-protein matches in herbivoreattacked tomato leaves.…”
Section: Future Perspectivesmentioning
confidence: 99%